Pretrial Diversion for Intrafamilial Child Sexual Offending: Does Biological Paternity Matter? - Titcomb, Caroline; Goodman-Delahunty, Jane; De Puiseau, Berenike Waubert (Criminal justice and behavior, 2012)
Diversion programs are generally reserved for offenders rated as low risk. The scant recidivism data on incest offenders classify intrafamilial offenders as lower risk than extrafamilial pedophiles. Even so, few community-based treatment programs accommodate offenders who sexually abuse children. Access to treatment programs for intrafamilial offenders is rare. Using a sample of 214 intrafamilial offenders who pled guilty on referral to a community-based pretrial diversion program for intrafamilial offenders, the authors explored whether biological fathers, typically classified as incest offenders, and nonbiological fathers, traditionally classified as extrafamilial pedophiles, benefited equally from diversion. Biological and nonbiological fathers were systematically compared to determine whether diversion programs should take the victim’s relationship to the offender—biological or nonbiological—into account when determining diversion eligibility. Effect sizes confirmed that the two subgroups of intrafamilial offenders were substantially similar on demographic features, characteristics of the index victim and index offense, and prior offending history. The victim–offender relationship was unrelated to acceptance into treatment, treatment completion, and sexual reoffending. These findings advance knowledge of sex offender subtypes and indicate that policies and practices that distinguish biological from nonbiological father offenders should be reconsidered. At a minimum, exclusion of nonbiological intrafamilial sex offenders from community-based treatment programs appears unwarranted.